Analisis Narasi dan Storytelling dalam Iklan Digital Shopee di YouTube - Rabiah Isti Maesaroh Arrasyid; Nawiroh Vera (Institut Nalanda, 2026)
This study examines the narrative structure and storytelling techniques in the Shopee Big Ramadan Sale 2023 advertisement on YouTube. Using a qualitative approach with descriptive-interpretive analysis, the research explores how storytelling influences consumer perception and emotional engagement. Data were collected through documentation and visual text observation, encompassing narrative elements, dialogue, character, gestures, color, background music, and on-screen text. Data analysis followed the model proposed by Miles & Huberman (1992), comprising three stages: data reduction, data display, and conclusion drawing. The findings reveal that storytelling in the Shopee advertisement was constructed through a simple yet culturally relevant narrative, integrating Ramadan values such as solidarity, care, and togetherness. The presence of public figures Komeng and Wika Salim strengthened emotional bonds between the audience and the brand. Visual and audio elements, including warm colors, religious-nuanced music, and Ramadan-themed visuals deepened the emotional meaning conveyed. The use of YouTube as a distribution platform enhanced the effectiveness of storytelling through dynamic audio-visual content and interactive features. Overall, this study confirms that storytelling is a key strategy in digital marketing communication, capable of increasing brand recall, shaping positive brand perception, and influencing consumer purchase intention.